In a complementary angle relationship, the sum of the angles is equal to 90 degrees.
So, the equation for the angle measures is:
(2x+3)° + 2x° = 90°
A figure shows two nonadjacent angles with measures (2x+3)° and 2x° . If the angles are complementary, what is the equation for the angle measures?(1 point)
(__)° + 2x° = __°
11 answers
Two complementary angles have measures (2x)° and (3x)°. What is the value of x and the two angle measures?
x = __, (2x)° = __°, and (3x)° = __°
x = __, (2x)° = __°, and (3x)° = __°
In a complementary angle relationship, the sum of the angles is equal to 90 degrees.
So, we can set up the equation:
(2x)° + (3x)° = 90°
Combining like terms, we have:
5x° = 90°
To solve for x, we divide both sides of the equation by 5:
5x/5 = 90/5
x = 18
Now that we have the value of x, we can substitute it back into the equations to find the angle measures:
(2x)° = 2 * 18° = 36°
(3x)° = 3 * 18° = 54°
Therefore, x = 18, (2x)° = 36°, and (3x)° = 54°.
So, we can set up the equation:
(2x)° + (3x)° = 90°
Combining like terms, we have:
5x° = 90°
To solve for x, we divide both sides of the equation by 5:
5x/5 = 90/5
x = 18
Now that we have the value of x, we can substitute it back into the equations to find the angle measures:
(2x)° = 2 * 18° = 36°
(3x)° = 3 * 18° = 54°
Therefore, x = 18, (2x)° = 36°, and (3x)° = 54°.
Angles j and k are supplementary angles. What is m∠j if m∠k=117° ?
__°
__°
When two angles are supplementary, their sum is 180 degrees.
So, if m∠k = 117°, then:
m∠j + m∠k = 180°
Substituting in the known value:
m∠j + 117° = 180°
To solve for m∠j, we can subtract 117° from both sides:
m∠j = 180° - 117°
m∠j = 63°
Therefore, m∠j is 63°.
So, if m∠k = 117°, then:
m∠j + m∠k = 180°
Substituting in the known value:
m∠j + 117° = 180°
To solve for m∠j, we can subtract 117° from both sides:
m∠j = 180° - 117°
m∠j = 63°
Therefore, m∠j is 63°.
Two supplementary angles have measures m∠ABC=105° and m∠CBD=(3x−24)° . What is the equation to solve for x ?
(3x - 24)° +__° = __°
(3x - 24)° +__° = __°
If two angles are supplementary, their sum is 180 degrees.
So, we can set up the equation:
m∠ABC + m∠CBD = 180°
Substituting the known values:
105° + (3x - 24)° = 180°
To solve for x, we can subtract 105° from both sides:
3x - 24° = 180° - 105°
3x - 24° = 75°
To isolate x, we can then add 24° to both sides:
3x = 75° + 24°
3x = 99°
Finally, to solve for x, we divide both sides by 3:
x = 99° / 3
x = 33°
To find the equation,
(3x - 24)° + __° = __°
we substitute the value of x:
(3*33 - 24)° + __° = __°
(99 - 24)° + __° = __°
75° + __° = __°
Therefore, the equation to solve for x is (3x - 24)° + 75° = __°.
So, we can set up the equation:
m∠ABC + m∠CBD = 180°
Substituting the known values:
105° + (3x - 24)° = 180°
To solve for x, we can subtract 105° from both sides:
3x - 24° = 180° - 105°
3x - 24° = 75°
To isolate x, we can then add 24° to both sides:
3x = 75° + 24°
3x = 99°
Finally, to solve for x, we divide both sides by 3:
x = 99° / 3
x = 33°
To find the equation,
(3x - 24)° + __° = __°
we substitute the value of x:
(3*33 - 24)° + __° = __°
(99 - 24)° + __° = __°
75° + __° = __°
Therefore, the equation to solve for x is (3x - 24)° + 75° = __°.
fill in the last blank
The equation to solve for x is (3x - 24)° + 75° = __°.
To fill in the last blank, we can simplify the equation:
(3x - 24)° + 75° = __°
3x + 51° = __°
Therefore, the equation to solve for x is (3x - 24)° + 75° = 3x + 51°.
To fill in the last blank, we can simplify the equation:
(3x - 24)° + 75° = __°
3x + 51° = __°
Therefore, the equation to solve for x is (3x - 24)° + 75° = 3x + 51°.
Two angles are supplementary with measures m∠ACB=4x° and m∠BCD=(6x+50)° . What is the measure of ∠ACB ?
m∠ACB = __°
m∠ACB = __°
If two angles are supplementary, their sum is 180 degrees.
So, we can set up the equation:
m∠ACB + m∠BCD = 180°
Substituting the given angle measures:
4x° + (6x + 50)° = 180°
To solve for x, we can combine like terms and isolate it:
10x + 50° = 180°
Subtracting 50° from both sides:
10x = 180° - 50°
10x = 130°
Finally, dividing both sides by 10:
x = 130° / 10
x = 13°
Therefore, the measure of ∠ACB is:
m∠ACB = 4x° = 4 * 13° = 52°
So, we can set up the equation:
m∠ACB + m∠BCD = 180°
Substituting the given angle measures:
4x° + (6x + 50)° = 180°
To solve for x, we can combine like terms and isolate it:
10x + 50° = 180°
Subtracting 50° from both sides:
10x = 180° - 50°
10x = 130°
Finally, dividing both sides by 10:
x = 130° / 10
x = 13°
Therefore, the measure of ∠ACB is:
m∠ACB = 4x° = 4 * 13° = 52°